(untitled) (Journal of Libya for geographical studies, 2025)
The oil Valley is one of the important promising basins in Kirkuk governorate, as it is characterized by its seasonal water flow. Given the importance of this canyon and the interest in its rehabilitation potential, this study aims to provide results and recommendations based on a deep study of its characteristics. The study focuses on the flow of surface water and its cartographic modeling, representing a model of the relationships between the factors and processes of erosion and associated terrestrial phenomena. These characteristics include morphometric, analytical methods that study the phenomena occurring on the Earth’s surface, based on data taken from contour maps, satellites and field studies, such as digital elevation data DEM).) These data are of great importance in the creation of a geographical database of aquariums, allowing to draw the water network as a natural morphometric phenomenon. This network has a role in determining the optimal use of land within the basin. One of the main objectives of the study is to conduct a comprehensive quantitative analysis of the characteristics of the drainage network of the oil Valley Basin, focusing on understanding its hydrological significance. This analysis aims to improve our understanding of the natural and human processes affecting the basin, and how they affect the use of land and Water Resources.